The Black athlete as hero : American barrier breakers from nine sports - Dorinson, Joseph, 1936- (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2022)
"Part history, part biography, this study examines the black athlete's search to unify what W.E.B. DuBois called the "two unreconciled strivings" of African Americans--the struggle to survive in black society while adapting to white society. Black athletes have served as vanguards of change, challenging the dominant culture, crossing social boundaries and raising political awareness. Champions like Joe Louis, Jackie Robinson, Muhammad Ali, Jim Brown, Wilma Rudolph, Roberto Clemente, Althea Gibson, Arthur Ashe, Serena Williams, Kareem Abdul-Jabbar and LeBron James make a difference, even as many in the black community question the idea of athletes as role models. The author argues the importance of sports heroes in a panic-plagued era beset with class division and racial privilege"--
18. Charlie Scott and Michael Jordan -- 19. LeBron James and Kobe Bryant -- 20. Ora Washington, Lynette Woodard, Cheryl Miller, Lisa Leslie, Cynthia Cooper-Dyke, & Maya Moore -- Section 7. Golf, Hockey, Gymnastics -- 21. Tiger Woods, Willie O'Ree, and Simone Biles -- Conclusion -- Chapter Notes -- Bibliography -- Index
Description based on print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: African American athletes -- Political activity -- History; Sports -- Political aspects -- United States -- History; African American athletes -- Biography; Heroes -- United States -- Biography; African Americans -- Social conditions -- History; Racism against Black people -- History; Social classes -- United States -- History; United States -- Race relations -- History; African Americans -- Social conditions; Sportifs noirs américains -- Activité politique -- Histoire; Sports -- Aspect politique -- États-Unis -- Histoire; Sportifs noirs américains -- Biographies; Héros -- États-Unis -- Biographies; Noirs américains -- Conditions sociales; Racisme à l'égard des personnes noires -- Histoire; Classes sociales -- États-Unis -- Histoire; États-Unis -- Relations raciales -- Histoire; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies; SPORTS & RECREATION / History; African American athletes; African Americans -- Social conditions; Heroes; Race relations; Racism against Black people; Social classes; Sports -- Political aspects; United States; Biographies; History; Biographies; Biographies